VEGETATION TYPES IN THAC TIEN - DEO GIO NATURAL FOREST OF XIN MAN DISTRICT, HA GIANG PROVINCE - Van Phe, Phung; Duc To Luu, Nguyen; Duy Hung, Vuong (Journal of Forestry Science and Technology, 2019)
forest, Xin Man district, Ha Giang province. The results of this research showed that the vegetation in the study area can be classified and characterized by nine major formations and three subformations, including: (1) Tropical evergreen seasonal submontane forests, (2) Tropical bamboo forests on the low mountains, (3) Evergreen broad-leaved woodlands regenerated after logging, (4) Evergreen broad-leaved woodlands regenerated after shifting cultivation and forest fires, (5) Evergreen broad-leaved shrublands with immature dicotyledonous trees, (6) Low bamboo thickets, (7) Short-grass communities with shrubs and without woody trees, (8) Mainly tall perennial flowering forbs, and ferns, and (9) Fern thickets. Of these, the formation of the tropical evergreen seasonal sub-montane forest is divided into two sub-formations: (i) Broad-leaved submontane forest lightly disturbed by human activities, (ii) Broad-leaved submontane forest heavily disturbed by human activities; mainly tall perennial flowering forbs, and ferns with one subformation: (iii) Forb communities of Musa acuminata.